Common Reflection Surface Stack Imaging of the Proterozoic Chambal Valley Vindhyan Basin and Its Boundary Fault in the Northwest India: Constraints on Crustal Evolution and Basin Formation. Issue 5 (15th May 2018) - Mandal, Biswajit; Vaidya, Vijaya Rao; Sen, Mrinal K.; Periyasamy, Karuppannan; Sarkar, Dipankar
Abstract: The Vindhyan basin of northwestern and central India is one of the largest undeformed Meso‐Neoproterozoic basins in the world with likely potential of hydrocarbons. Crustal seismic reflection data along a 165‐km long Chandli‐Bundi‐Kota‐Kunjer profile of the Chambal Valley Vindhyan basin processed using common reflection surface stack method brought out new crustal features, which were missing in earlier images. A gently dipping structure of the basin is imaged with a maximum of 7.5‐km thick Proterozoic sediments, 1.5‐km thick volcanic sequence, and the granitic basement at 9.0‐km depth. The Great Boundary Thrust, a NW dipping crustal‐scale regional tectonic feature outcropping at Bundi, and a new NW dipping reflection band from 9‐ to 30‐km depth, named here as the Chambal thrust, are imaged beneath Bundi‐Kota segment. Subduction and collision are responsible for evolution of these thrusts implying horizontal crustal growth. Seismic images of compression on one side and extension on another side along with differences in the Moho characteristics and other constraints from geophysical data around Kota indicate the presence of a new tectonic boundary with a strong lateral discontinuity and strike‐slip features. The Moho topography is delineated for the first time revealing a crustal thickness ranging from 40 to 44 km. A 9‐ to 12‐km thick mafic underplating at the lower crust suggests an important postcollisional process indicating vertical crustal growth. Based on the images from the present reflection study, a geodynamic model of the region is suggested in a plate tectonic framework, which may apply to similar Paleoproterozoic collisional areas and associated basin formation. Key Points: Basement structure of hydrocarbon‐prospective Proterozoic Vindhyan basin is delineated New plate tectonic evolutionary model for intracratonic basin is suggested Constrains on crustal evolution and basin formation are determined